2018
DOI: 10.1002/1873-3468.12940
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial fatty acid biosynthesis and muscle fiber plasticity in very long‐chain acyl‐CoA dehydrogenase‐deficient mice

Abstract: The white skeletal muscle of very long-chain acyl-CoA-dehydrogenase-deficient (VLCAD ) mice undergoes metabolic modification to compensate for defective β-oxidation in a progressive and time-dependent manner by upregulating glucose oxidation. This metabolic regulation seems to be accompanied by morphologic adaptation of muscle fibers toward the glycolytic fiber type II with the concomitant upregulation of mitochondrial fatty acid biosynthesis (mFASII) and lipoic acid biosynthesis. Dietary supplementation of VL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…Similar to the observations in humans, long‐term treatment studies VLCAD −/− mice demonstrated that triheptanoin was indeed able to supply enough energy at rest . In addition, the metabolic and morphologic trans‐differentiation towards the glycolytic muscle fibres type II observed as progressive adaptive mechanism was not reversed by the supplementation with this compound . On the other hand, at the cardiac level, although triheptanoin was not able to prevent the impairment of cardiac function, it did not contribute to progression of cardiac dysfunction in dilated cardiomyopathy in contrast to the regular MCT, similar to data reported for FAOD patients .…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to the observations in humans, long‐term treatment studies VLCAD −/− mice demonstrated that triheptanoin was indeed able to supply enough energy at rest . In addition, the metabolic and morphologic trans‐differentiation towards the glycolytic muscle fibres type II observed as progressive adaptive mechanism was not reversed by the supplementation with this compound . On the other hand, at the cardiac level, although triheptanoin was not able to prevent the impairment of cardiac function, it did not contribute to progression of cardiac dysfunction in dilated cardiomyopathy in contrast to the regular MCT, similar to data reported for FAOD patients .…”
Section: Methodssupporting
confidence: 86%
“…47 In addition, the metabolic and morphologic trans-differentiation towards the glycolytic muscle fibres type II observed as progressive adaptive mechanism was not reversed by the supplementation with this compound. 48 On the other hand, at the cardiac level, although triheptanoin was not able to prevent the impairment of cardiac function, it did not contribute to progression of cardiac dysfunction in dilated cardiomyopathy in contrast to the regular MCT, similar to data reported for FAOD patients. 43,47,49 Moreover, long-term supplementation of triheptanoin induced de novo lipogenesis and elongation of fatty acids leading to the alteration of the fatty acid profiles in several tissues characterised by a strong reduction of polyunsaturated fatty acids and the marked increase of monounsaturated species.…”
Section: Triheptanoin In Long-chain Fatty Acid Disorderssupporting
confidence: 72%
“…In addition, the glycolysis/gluconeogenesis, closely related to skeletal muscle fiber types, is significantly enriched. Moreover, fatty acid metabolism and fatty acid degradation pathways are also significantly enriched, while recent studies found that the change of fatty acid composition was accompanied by the transformation of skeletal muscle fiber types [40,41]. Thus, it will be interesting to investigate the specific regulatory mechanisms of the skeletal muscle fiber types and fatty acid composition mediated by the DE lncRNAs identified in this study.…”
Section: Discussionmentioning
confidence: 80%
“…Peptides were extracted from the gel slices with ethanol and resulting peptide mixtures were processed on STAGE tips as described [34]. Sample analysis, data acquisition and processing were performed as previously described [35].…”
Section: Methodsmentioning
confidence: 99%